Access to Blood Glucose Testing in Peru: Who Is Getting Tested? - Jamee Guerra Valencia; Akram Hernández-Vásquez; Carlos Rojas-Roque; Rodrigo Vargas-Fernández (Epidemiologia, 2025)
Background/Objectives: Significant disparities in access to diabetes screening persist, particularly among populations with limited healthcare access. We aimed to estimate the proportion of overweight-obese Peruvian adults who underwent blood glucose testing (BGT) in the past year and to analyse the socioeconomic and geographic inequalities associated with access to this preventive intervention. Methods: We conducted a cross-sectional study using data from the Demographic and Family Health Survey 2023. We included adults aged 35–70 years diagnosed with overweight or obesity, according to the United States Preventive Services Task Force screening recommendation. We used concentration curves (CC) and concentration indices (CI) to assess socioeconomic inequalities in BGT. BGT was ascertained using a self-reported question, while the wealth index was used as the variable to measure inequality. We also conducted a decomposition analysis to determine the relative contributions of covariates to socioeconomic inequalities in BGT. Results: A total of 9499 individuals were included in the analysis. A pro-rich concentration of BGT uptake was observed in CC and CI (0.2090; p < 0.001). Notably, a 27-point prevalence difference was reported between the lowest and highest wealth index. The decomposition analysis showed that higher education (+64%) and rural areas (+10.6%) were the main contributors to this pro-rich concentration. In contrast, secondary education (−4.7%) and female gender (−3.4%) reduced this pro-rich concentration. Conclusions: The results underscore the need for targeted strategies, such as enhancing healthcare infrastructure and implementing localized screening initiatives, to close the gap and address the burden of undiagnosed diabetes in high-risk populations.